Conservative Iron Chelation for Neuroferritinopathy. Issue 9 (22nd August 2022) - Marchand, Felix; Moreau, Caroline; Kuchcinski, Gregory; Huin, Vincent; Defebvre, Luc; Devos, David
Abstract: Background: Neuroferritinopathy is a rare inherited neurodegenerative disease with brain iron accumulation characterized by brain iron overload resulting in progressive movement disorders. No treatment is currently available. Objective: We assessed conservative iron chelation with deferiprone at 30 mg/kg/day on the disease progression with controlled periods of discontinuation. Methods: Four patients with confirmed molecular diagnosis of neuroferritinopathy were given deferiprone at different stages of disease progression and with clinical and biological monitoring to control benefit and risk. Results: The four patients showed slight to high improvement. In one case, we managed to stabilize disease progression for more than 11 years. In another case, we were able to reverse symptoms after a few months of treatment. The earliest the treatment was started, the most efficient it was on disease progression. Conclusions: Conservative iron chelation should be further assessed in neuroferritinopathy. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.